A study of the effect of question feedback types on learning engagement in panoramic videos - Huang, Guan; Zhang, Haohua; Zeng, Jingsheng; Chen, Wen (Frontiers in Psychology, 2025)
IntroductionThe immersive and interactive nature of panoramic video empowers learners with experiences that are infinitely close to the real environment and increases the use of imagination in learners’ knowledge acquisition. Studies have shown that embedding question feedback in traditional educational videos can effectively improve learning. However, little research has been conducted on embedding question feedback in panoramic videos to explore what types of question feedback effectively improve the dimensions of learners’ learning engagement and yield better learning experiences and learning effects.MethodsThis study embedded questions with feedback within panoramic videos by categorizing feedback into two types: simple feedback and elaborated feedback. Using eye tracking, brainwave meters, and subjective questionnaires as measurement tools, this study investigated which type of question feedback embedded in panoramic videos improved various dimensions of learner engagement and academic performance. Participants (n = 91) were randomly assigned to the experimental group (simple feedback, elaborated feedback) or the control group (no feedback).ResultsThe results of the study showed that (1) the experimental group significantly improved in cognitive engagement, behavioral engagement, and emotional engagement compared to the control group. When the precision of feedback information was greater, the learner’s behavioral engagement was greater; however, the precision of feedback information did not significantly affect cognitive and emotional engagement. (2) When the feedback information was more detailed, the learners’ academic performance was better.DiscussionThe findings of this study can support strategic recommendations for the design and application of panoramic videos.